The Effects of On-Demand Behavior in Routing Protocols for Multi-Hop Wireless Ad Hoc Networks - Maltz, Dave; Broch, Josh; Jetcheva, Jorjeta; Johnson, David B. (IEEE Journal on Selected Areas in Communications, 1999)
A number of different routing protocols proposed for use in multihop wireless ad hoc networks are based in whole or in part on what can be described as on-demand behavior. By on-demand behavior, we mean approaches based only on reaction to the offered traffic being handled by the routing protocol. In this paper, we analyze the use of on-demand behavior in such protocols, focusing on its effect on the routing protocol's forwarding latency, overhead cost, and route caching correctness, drawing examples from detailed simulation of the dynamic source routing (DSR) protocol. We study the protocol's behavior and the changes introduced by variations on some of the mechanisms that make up the protocol, examining which mechanisms have the greatest impact and exploring the tradeoffs that exist between them.